Description of Platelet Count Patients Infected with Corona Virus (Covid-19) with Grouping of Productive and Elderly Age - Hapipah Hapipah; Anik Handayati; Nur Vita Purwaningsih (International Journal of Advanced Health Science and Technology, 2022)
Routine hematology tests are one of the supporting tests in diagnostics to assess the severity of the disease and predict risk in COVID-19 patients, and can be used as supporting data on RT-PCR tests. Some blood tests that are widely used as monitoring tools and predicators of COVID-19 are the number of leukocytes, the  number of lymphocytes, the number of neutrophils, the  number of platelets and NLR (Neutrophil lymphocyte ratio).  Thrombocytopenia occurs due to excessive use of tromocytes in the body as compensation for damage to lung parenchym cells, the lungs are organs where platelets are released from megacaryocytes, so this damage causes disruption of platelet maturation process. The type of research used is quantitative descriptive with the aim to find out the results of blood tests complete with platelet parameters in patients infected with the COVID-19 coronavirus at Muhammad Noer Pamekasan General Hospital. The results of the study were platelet count test results at normal productive age of 67 respondents (96%) and decreased platelet count (Thrombocytopenia) by 3 respondents (4%). While in normal elderly age a number of 26 respondents (87%) and a decreased platelet count (Thrombocytopenia) amounted to 4 respondents (13%).